Riparian forest fragments in rice fields under different management: differences on hymenopteran parasitoids diversity - Silva,G. S. (2020)
Abstract Hymenopteran parasitoids are important biological control agents in agroecosystems, and their diversity can be increased with habitat heterogeneity. Thus, the purpose of the study is to evaluate the influence of distance of rice-growing areas from natural fragment, type of crop management (organic and conventional) and crop stages (vegetative and reproductive stages) on parasitoids family diversity. The work took place in two irrigated rice crops, one with organic management (O.M.) and another one with conventional management (C.M.), in the municipality of Nova Santa Rita, RS, Brazil, during the 2013/2014 and 2014/2015 seasons. The parasitoids were collected with Malaise trap arranged at different distances in relation to the native vegetation surrounding the rice crop in both places. Specimens were collected twice a month from seeding until the rice harvest. Average abundance between management, distances and rice development were compared. The most abundant families were Platygastridae, Mymaridae, Encyrtidae, Eulophidae and Trichogrammatidae. Parasitoid average abundance was significantly higher on OM only in the second season. There was a negative correlation between distance from native vegetation and parasitoid abundance in C.M. areas. There were differences in the composition of the parasitoid assembly between the phenological stages of rice.